IMPACT OF INDONESIAN DECENTRALIZATION ON POVERTY ALLEVIATION - ', Sutiyo (Jurnal Ilmu Administrasi Negara, 2016)
Impact of Indonesian Decentralization on Poverty Alleviation. This study aims to analyze the impact of decentralization on poverty alleviation. To understand how decentralized programs have impact on various dimensions of poverty, this study uses a case study in Serang, Kedarpan and Sumilir villages in Purbalingga district, Central Java province. The study population was household. Samples taken were 10% of households randomly from each study village. Data are collected through observation, interview, questionnaire and documentary study. Positive impacts of decentralization are found more in terms of access to public service and infrastructure improvement, but less in income generation and social protection. Among various decentralized poverty alleviation programs, geographically targeted program like National Program for Community Empowerment is more successful compared to individually targeted program like Raskin, Askeskin, Poor House Renovation Program, and Program of Woman Saving Group.